2017
DOI: 10.1039/c7nr01853c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PEGylated hollow gold nanoparticles on stem cell migration: potential application in tissue regeneration

Abstract: Mesenchymal stem cells (MSCs) not only can be differentiated into different cell types but also have tropism towards injured or inflamed tissues serving as repair cells. Here we have demonstrated that MSCs containing gold nanoparticles (GNPs) whose surface has been functionalized with PEG show accelerated cell migration, successful scaffold colonization and regeneration. We report the impact of GNPs on the migration (by the wound healing assay), and proliferation (by flow cytometry analysis and by the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…4Cindicates that an average uptake of 0.14 ng of Au per cell was measured when PEG-HGNs were incubated for 24 h (corresponding to more than 600000 PEG-HGNs per cell). The higher internalization of PEG-coated particles compared to their uncoated counterparts has been reported previously for different cell lines (MSCs or tumoral cells) and attributed to a facilitated uptake thanks to the increase of NPs stability and reduced agglomeration provided by the PEG coating 45,46.…”
supporting
confidence: 60%
“…4Cindicates that an average uptake of 0.14 ng of Au per cell was measured when PEG-HGNs were incubated for 24 h (corresponding to more than 600000 PEG-HGNs per cell). The higher internalization of PEG-coated particles compared to their uncoated counterparts has been reported previously for different cell lines (MSCs or tumoral cells) and attributed to a facilitated uptake thanks to the increase of NPs stability and reduced agglomeration provided by the PEG coating 45,46.…”
supporting
confidence: 60%
“…Due to the easy of functionalization of gold nanoparticles with thiolated chains, PEG is one of the most used biocompatible molecules for increasing the biocompatibility of gold nanomaterials. Several studies have described the influence of PEGylated gold nanoparticles on cell metabolism, cell cycle progression [63,64] and in the induction of apoptosis [64] in both healthy and cancer cell lines. Regarding cell viability, these studies reported similar effects in the cell types assayed as those showed by our previously reported HGNPs, pointing to 0.1 mg/mL as the subcytotoxic concentration [63], while a concentration of 10 mM (2 mg/mL) PEG-AuNPs was clearly harmful for human chronic myeloid leukemia cell line K562 exerting viability percentages around 20% [64].…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Several studies have described the influence of PEGylated gold nanoparticles on cell metabolism, cell cycle progression [63,64] and in the induction of apoptosis [64] in both healthy and cancer cell lines. Regarding cell viability, these studies reported similar effects in the cell types assayed as those showed by our previously reported HGNPs, pointing to 0.1 mg/mL as the subcytotoxic concentration [63], while a concentration of 10 mM (2 mg/mL) PEG-AuNPs was clearly harmful for human chronic myeloid leukemia cell line K562 exerting viability percentages around 20% [64]. Also, a previous study showed that the interaction of nanoparticles on cell cycle varied depending on both cell line and nanoparticle type.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Polyethylene glycol is one of the most used NP stabilizing polymer and the gold standard for "stealth" polymers in the emerging area of polymer-based drug carriers, gene vectors, imaging, therapeutic agents, bio-sensing, and tissue regeneration [65,66].…”
Section: Applications Of Pegylated Nanoparticlesmentioning
confidence: 99%